2012
DOI: 10.1016/j.mce.2011.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptors in vascular function and disease

Abstract: The mineralocorticoid receptor (MR), a member of the steroid receptor family, regulates blood pressure by mediating the effects of the hormone aldosterone (Aldo) on renal sodium handling. Over the past decade, it has become clear that MR is expressed in the cardiovascular system and interest has grown in understanding the direct role of the MR in regulating vascular function and contributing to cardiovascular disease. This interest stems from multiple clinical studies in which drugs that decrease MR activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(172 citation statements)
references
References 125 publications
5
163
0
1
Order By: Relevance
“…Excessive aldosterone/MR signaling may be deleterious for vessels, as impaired vascular reactivity observed in subjects with aldosterone-producing adrenal adenoma, hypertension, or heart failure can be improved by the use of MR antagonists (4,20,21). It has been suggested that the vascular pathological effects of aldosterone/MR result from inflammation, increased vascular reactive oxygen species, and decreased nitric oxide production (4,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive aldosterone/MR signaling may be deleterious for vessels, as impaired vascular reactivity observed in subjects with aldosterone-producing adrenal adenoma, hypertension, or heart failure can be improved by the use of MR antagonists (4,20,21). It has been suggested that the vascular pathological effects of aldosterone/MR result from inflammation, increased vascular reactive oxygen species, and decreased nitric oxide production (4,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the vascular pathological effects of aldosterone/MR result from inflammation, increased vascular reactive oxygen species, and decreased nitric oxide production (4,22,23). Such mechanisms are observed in animal models when mineralocorticoid pathway activation is associated with nephrectomy and salt excess, ischemia, or pressure overload (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells are involved in the induction of vascular calcification, and aldosterone has detrimental effects on the endothelium and the vasculature (40,41). Aldosterone downregulates eNos, an effect reversed by spironolactone (30).…”
Section: Figurementioning
confidence: 99%
“…Lately, studies have demonstrated the presence of mineralocorticoid receptors (MR) in nonepithelial tissues, including heart and blood vessels (42). Aldosterone was reported to contribute to vascular remodeling and endothelial dysfunction through several coupling mechanisms (8,13,23), all associated with heightened vascular tone. Paradoxically, the increase in aldosterone levels in pregnancy occurs together with decreased vascular resistance (10), indicating that gestation resets some of the physiological responses normally consequent to an enhanced RAA system.…”
mentioning
confidence: 99%